Bioefficacy of various strains of Trichoderma and Pseudomonas spp. against damping-off of cauliflower - CHOUDHARY, AJAY KUMAR; SINGH, NARINDER; SINGH, DALJEET; RAINA, SHIVETA (The Indian Journal of Agricultural Sciences, 2019)
Trichoderma and Pseudomonas strains were tested against damping-off of cauliflower (Pythium aphanidermatum and Rhizoctonia solani). Dual culture antagonism assays were carried out on potato dextrose agar and King’s B medium to determine the effect of Trichoderma and Pseudomonas strains respectively, on mycelial growth of the pathogens. Antagonistic effect on P. aphanidermatum and R. solani was 53.1 and 44.6% respectively by T. harzianum (Th5) where as P. fluorescens (Pf3) showed maximum inhibition against P. aphanidermatum and R. solani of 60 and 70% respectively. Finally, the selected potent strains of Trichoderma spp (Th5 and Tv1) and P. fluorescens Pf3, were evaluated on cauliflower seedling development and as a potential antagonist for controlling cauliflower dampingoff caused by P. aphanidermatum and R.solani, under field conditions. T. harzianum (Th5) resulted significantly reduction in damping off disease, promoted the plant growth and enhanced the yield.